BREXIT: CAUSES AND EXPECTED EFFECTS - Bugarčić, Filip Ž; Simić, Marijana N (International Journal of Economic Practice and Policy, 2020)
The integration of countries and the formation of the common market, represent a desirable form of trade development and improving the level of development of individual economies. An example of a common market on the territory of Europe is the European Union, which has a unique legal and economic system applied by all member countries, as well as a unique system of customs and non-tariff barriers to non-member countries. After the referendum held in June 2016, when the UK began the exit from EU, it turned out that not all countries shared the same views on the benefits from economic integration. Approximately 52% of citizens voted for exiting the EU when the withdrawal of this island country from the economic and political community of the European countries began. The aim of this paper is to identify the potential reasons for and effects of abandoning economic integration, based on Brexit case, as well as an assessment of the economic trends and effects that will occur in this particular case. Based on the results of the analyses carried out and collected secondary data, we can conclude that the causes and positive impact of Brexit will be felt only if the UK finds the best way for exiting the EU, which will almost certainly require a high degree of liberalization and maintenance of economic relations with the EU. This will enable the reduction of adverse effects, provide chances for the emergence of positive effects and justify the purpose of disintegration.
Keywords: Brexit; European Union; Great Britain; economic integration; economic disintegration; common market; effects; reasons